Dual-Focused Transformational Leadership, Teachers’ Satisfaction of the Need for Relatedness, and the Mediating Role of Social Support - Schoch, Simone; Keller, Roger; Buff, Alex; Maas, Jasper; Rackow, Pamela; Scholz, Urte; Schüler, Julia; Wegner, Mirko (Frontiers in Education, 2021)
Basic psychological need satisfaction is essential for teachers’ well-being and motivation at work. Transformational leadership contributes to the development and maintenance of a respectful, constructive atmosphere, a supportive working climate, and has been suggested to be a crucial factor for employees’ satisfaction of the need for relatedness. Transformational leadership is also considered as an ideal leadership style in the school setting. But most studies did not distinguish between individual and team effects of this leadership behavior. In the present study, we applied the dual-focused model of transformational leadership and focused on social processes to address the question of whether individual- and group-focused transformational leadership behavior contribute differently to teachers’ satisfaction of the need for relatedness. Based on longitudinal data with three measurement points across one school year of N = 1217 teachers, results of structural equational models supported the notion of the dual effects of transformational leadership: Individual-focused transformational leadership was directly positively related to teachers’ change in satisfaction of the need for relatedness. The relationship between group-focused transformational leadership and change in satisfaction of the need for relatedness was mediated by received social support from team members. These findings emphasize the importance of school principals’ leadership behavior for teachers’ satisfaction of the need for relatedness. The satisfaction of the need for relatedness is therefore not only satisfied through the direct interaction between the school principal and the individual teacher, but also through interactions of the school principal with the whole team. Our results confirm that school principals should focus their leadership behavior both on teachers’ individual need satisfaction as well as on team development.